PENGARUH MANAJEMEN KELAS TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS VIII SMP - Naslawati, Naslawati (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2026)
This study aims to determine the effect of classroom management on mathematics learning outcomes of eighth-grade students at SMP IT Zurriyatul Qurani Almaarif, Lhokseumawe City. The research employed a quantitative approach with a correlational research design. The population and sample consisted of all eighth-grade students totaling 28 students using saturated sampling technique. Data collection was conducted through a classroom management questionnaire with 25 statement items using a Likert scale and documentation of mathematics grades. Data analysis techniques included descriptive statistics, prerequisite tests (normality and linearity), and simple linear regression analysis. The results showed that classroom management was in the good category with an average score of 97.43, and mathematics learning outcomes had an average of 79.82 with a mastery level of 75%. There was a positive and significant effect of classroom management on mathematics learning outcomes with a t-value of 8.273 > t-table 2.056 and significance of 0.000 < 0.05. The coefficient of determination of 0.612 indicates that classroom management contributes 61.2% to students' mathematics learning outcomes, while 38.8% is influenced by other factors. The regression equation Y = 24.156 + 0.571X shows that every one-unit increase in classroom management score will improve mathematics learning outcomes by 0.571 units. ABSTRAK Penelitian ini bertujuan untuk mengetahui pengaruh manajemen kelas terhadap hasil belajar matematika siswa kelas VIII SMP IT Zurriyatul Qurani Almaarif Kota Lhokseumawe. Penelitian menggunakan pendekatan kuantitatif dengan jenis penelitian korelasional. Populasi dan sampel penelitian adalah seluruh siswa kelas VIII yang berjumlah 28 siswa dengan menggunakan teknik sampling jenuh. Pengumpulan data dilakukan melalui angket manajemen kelas dengan 25 item pernyataan menggunakan skala Likert dan dokumentasi nilai matematika. Teknik analisis data menggunakan statistik deskriptif, uji prasyarat (normalitas dan linearitas), dan analisis regresi linear sederhana. Hasil penelitian menunjukkan bahwa manajemen kelas termasuk kategori baik dengan skor rata-rata 97,43 dan hasil belajar matematika memiliki rata-rata 79,82 dengan tingkat ketuntasan 75%. Terdapat pengaruh positif dan signifikan antara manajemen kelas terhadap hasil belajar matematika dengan nilai t hitung 8,273 > t tabel 2,056 dan signifikansi 0,000 < 0,05. Koefisien determinasi sebesar 0,612 menunjukkan bahwa manajemen kelas memberikan kontribusi sebesar 61,2% terhadap hasil belajar matematika siswa, sedangkan 38,8% dipengaruhi oleh faktor lain. Persamaan regresi Y = 24,156 + 0,571X menunjukkan bahwa setiap peningkatan satu satuan skor manajemen kelas akan meningkatkan hasil belajar matematika sebesar 0,571 satuan